Partisipasi Petani Garam dalam Pengelolaan Hutan Mangrove di Kelurahan Kotauneng Kabupaten Sikka - Warsiyah Warsiyah; Gabriel Otan Apelabi (Fakultas Pertanian, Universitas Nusa Nipa, 2026)
In Sikka district, mangrove trees to make boats and taken as a source of firewood. The main use of mangrove wood for fuel is drying salt. As a result of this activity can be seen in the mangrove forest area there are many large stumps from trees that were taken as evidence. The method used is descriptive method. In addition to the descriptive method of collecting the data is also used questionnaires or interviews with the respondents as well as direct observation. The results showed that the level of participation of the community preservation salt farmers are at a good level, level of community participation in conservation activities showed that 15.93% of salt farmers have a high participation rate preservation, 60.37% salt farmers have participation rates that are conservation and 23.70% salt farmers have a low participation rate preservation. The average utilization rate of mangrove forest communities will address that 7.41% salt farmers have a high utilization rate, 40.74% had a moderate level of utilization and 51.85% have a low utilization rate.